Fontes lipídicas e ácidos graxos essenciais no desenvolvimento ovariano e desempenho reprodutivo de jundiás Rhamdia quelen - Hilbig, Cleonice Cristina [UNESP] (2015)
Broodstock nutrition is one of the main aspects related with the quality of eggs and larvae produced. Lipids and its fatty acid composition are considered important on gonadal development, gonadotropic and steroid hormones, as well as influencing the formation of biological structures including cell membranes. In fish linoleic and linolenic are the essential fatty acids, which mabe converted into polyunsaturated fatty acids, like ARA, EPA and DHA, respectively. The marine fish oil are good sources of polyunsaturated fatty acids, however, vegetable oils are more communly used in fish diets. Thus, the aim of this study was to evaluate the ovarian and reproductive development of silver catfish (Rhamdia quelen) fed with lipid sources (soybean oil, marine fish oil, refined palm oil and a mixture). The lipid sources did not influence ovarian development, levels of estradiol, 17α-hidroxyprogesterona, and gonadosomatic index. However, the fatty acid changed fatty acid profile found in the liver, gonads and oocytes. Additionally, palm oil give rise to better fertilization rates and are recommended, suggesting that it may be used for fish oil replacement